Identification of MADS-box Gene in Oil Palm (Elaeis guineensis Jacq.) - Nawfetrias, Winda; Sobir,; Faizal, Irvan (UI Scholars Hub, 2016)
The bunch size represented by the fruit number is the main parameter of oil palm (Elaeis guineensis Jacq.) yield. The fruit number, which is determined during the initial phase of development, is related to various factors, including the genetic properties of the trees. Trees that have more pistillate flowers have more fruit. The diversity of MADS-box genes assumed can be used as a marker for trees that have a higher number of pistillate flowers. Therefore, the aims of this research were to isolate and identify the MADS-box genes from flowers of tenera oil palm using PCR techniques. The SQUAMOSA (SQUA) gene and the GLOBOSA (GLO) gene are members of the MADS-box genes family that are responsible for sepal, petal and stamen organ development. The genomic DNA of the staminate flowers of trees that have more staminate flowers (P1) and the genomic DNA of the pistillate flowers of trees that have more pistillate flowers (P2) were isolated using the CTAB+ PVP method. The CTAB+PVP method was more efficient for isolating pistillate flower genomic DNA than staminate flower genomic DNA. The genomic DNA of P1 and P2 was amplified with two primers: BMS and BMG. The BMS primers gave a PCR product size of 1250 bp for the genomic DNA of P1 and P2. Meanwhile, the BMG primers gave a PCR product size of 1250 bp and 1300 bp for P1 and P2, respectively. The PCR products were sequenced and analyzed for homology using the GenBank database. BLAST analysis showed the PCR products have high homology with the SQUA1 gene and the GLO2 gene. Alignment analysis showed that the DNA fragments amplified with the BMS primers of the P1 and P2 sequences have variations in the exons and introns, and the variations were observed only in the introns of the DNA fragments amplified with the BMG primers.